Association of Cardiovascular Disease with the Metabolic Syndrome in a Predominantly Male Cohort with Rheumatoid Arthritis - Kerr, G.S.; Sabahi, I.; Richards, J.S.; Mikuls, T.R.; Rangan, B.V.; Reimold, A.; Cannon, G.W.; Johnson, D.; Caplan, L. (IntechOpen, 2012)
None